A Critical Reflection: Exposing Whiteness in Child Welfare Practice - Kalvari, Lauren (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2022)
This critical reflection is based on my practice encounter as a white settler social worker within the context of Child Welfare, in rural Canada during the late 1990s. This paper is in line with Karen Healy’s (2001) notion of critical social work, as a means to enhance systemic and related child welfare social worker practice. More specifically this paper addresses, through a specific case encounter with an Indigenous mother, how white settler social workers are systemically entangled in perpetuating acts of oppression. This critical reflection enables the reader to become aware of how mainstream social work practice, has the ability to unintentionally harm those service receivers that it actually intends to help. This paper critically addresses discourse around professional innocence, the risks of professional knowledge, representational violence and ethical practice dilemmas, within the context of a disguised practice encounter. The relevance of this critical reflection may be seen as a social justice initiative, catered predominantly towards white settler front line practitioners. These challenges are originating from within our own practices. Our practices are historically embedded in systemic colonial forms of discrimination and racism against First Nations, Métis and Inuit communities. I bring light to how white settler social workers should confront their own personal and professional pre-conceived notions, biases, and misconceptions and instead, implement anti-racist and anti-discriminatory practices within their work. This process begins with critical self-reflection.